Assessment of agronomic potential of land resources within the Gadana watershed in Northeast Nigeria, based on the analysis of soil and physiographic attributes - Chiroma, Alhaji Maigana; Adamu, Ibrahim; Lawal, Abubakar Abdullahi; Goni, Ibrahim Baba; Ibrahim, Yusuf (International Journal of Sustainable Agricultural Research, 2025)
This research aimed to evaluate the potential of land resources within the Gadana watershed for their suitability to support intensive agriculture. Land suitability assessments for surface irrigation and rain-fed cropping were conducted using topography and soil physical and chemical properties as primary evaluation criteria. Surface soil samples from the potentially irrigable segment of the watershed were collected and analyzed for selected physical and chemical properties using standard analytical methods. The results showed highly variable soil textures, ranging from sandy loam to clay loam. The soil pH values ranged from 5.4 to 6.2; electrical conductivity (ECe) from 0.03 to 0.14 dS/m-1; organic carbon (OC) from 0.27 to 0.82%; total nitrogen (TN) from 0.10 to 0.22%; available phosphorus (AP) from 0.70 to 4.55 mg/kg; and cation exchange capacity (CEC) from 4.42 to 8.81 cmol (+) kg-1. Results revealed that a significant portion of the watershed, measuring up to 687.0 ha and 700.8 ha, falls under flat (47.19%) and gentle (48.14%) slopes, respectively, which are considered suitable for surface irrigation. The identified textural classes include sandy loam (SL) covering 174.74 ha (36.41%), sandy clay loam (SCL) covering 7.89 ha (1.60%), and clay loam (CL) covering 297.40 ha (61.98%). Only a small portion of the watershed was marginally suitable or unsuitable for intensive cropping. Therefore, the soils of the study area would require careful management to enable sustainable cropping. The main limitations are slope, soil texture, and fertility, which can be addressed through nutrient recycling and proper soil management practices.